Factors associated with urinary tract infection in a Nursing Home - João Luis Almeida da Silva; Cassiane Dezoti da Fonseca; Eniva Miladi Fernandes Stumm; Roseanne Montargil Rocha; Myria Ribeiro da Silva; Dulce Aparecida Barbosa (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objective: to analyze the factors associated with urinary tract infection occurrence in institutionalized elderly. Methods: this is a cross-sectional, analytical, quantitative study with 116 elderly people from a Nursing Home. Urinary tract infection diagnosis was carried out through urine culture and clinical assessment. Demographic data and associated factors were obtained from medical records. Statistical analysis included bivariate analysis and logistic regression models. Results: the factors associated with urinary tract infection (p<0.05) were being female; wheelchair user; diaper use; diuretic use; urinary and bowel incontinence; type 1 diabetes; benign prostatic hyperplasia; dehydration. Conclusion: this study revealed that it is important to consider non-modifiable factors such as sex and clinical comorbidities; however, dehydration, a modifiable factor, increased the chances of developing urinary tract infections by 40 times among institutionalized elderly and demands greater attention from the health team.